Programming Emotional Education and Prevention of Violence at the ESO (Journal of Parents and Teachers, 2014)
This article presents programs of emotional education and violence prevention made by  a group of teacher from Alicante, Spain. These programs are directed to secondary education students and should be included in the Tutorial Action Plan. The objectives are preventing violence in school from a practical proposal based on emotional education, proposing to teachers a practical method to intercede in conflict management, promoting among students the knowledge and regulation of emotions and favouring the class atmosphere.
Keywords: experiences; school coexistence; emotional education; violence prevention.